Formation of Orion fingers. Issue 1 (15th May 2020) - Dempsey, Ross; Zakamska, Nadia L; Owen, James E
ABSTRACT: 'Orion fingers' are a system of dozens of bow shocks, with the wings of shocks pointing to a common system of origin, which is centred on a dynamically disintegrating system of several massive stars. The shock heads propagate with velocities of up to 300–400 km s −1, but the formation and physical properties of the 'bullets' leading the shocks are not known. Here, we summarize two possible scenarios for the formation of the 'bullets' and the resulting bow shocks ('fingers'). In the first scenario, bullets are self-gravitating, Jupiter-mass objects that were formed rapidly and then ejected during the strong dynamical interactions of massive stars and their discs. This scenario naturally explains the similar time-scales for the outflow of bullets and for the dynamical interaction of the massive stars, but has some difficulty explaining the observed high velocities of the bullets. In the second scenario, bullets are formed via hydrodynamic instabilities in a massive, infrared-driven wind, naturally explaining the high velocities and the morphology of outflow, but the bullets are not required to be self-gravitating. The processes that created the Orion fingers are likely not unique to this particular star-forming region and may result in free-floating, high-velocity, core-less planets.